BALANCE IN INFANCY: COMPARATIVE STUDY BETWEEN PRACTITIONERS OF SWIMMING, FUTSAL AND GROUP IT HAS CONTROLLED (Fiep Bulletin - online, 2013)
Amongst the motor abilities, the balance, gift in the category of stabilizing movements, receives a bigger importance for the fact from all the other abilities of locomotive or manipulative character to need its maturates. The daily pay-porting study it comes to argue practical swimming and futsal as stimulations under the influence in the dynamic and static balance in children of 5 years. The research is descriptive comparative having as sample 24 children of 5 years of the masculine sex divided in: G1- 8 practitioners of swimming, G2- 8 practitioners of futsal and G3- 8 children of the group have controlled. It was carried through an evaluation of the maturational level of the balance in accordance with Gallahue and Ozum (2005) and a test of static balance and dynamic considered by Lefèvre (1972). The data handling was made through the descriptive statistics. An excellent result in the performance of the balance, the children of the practicing groups of futsal and swimming was observed (this with an index of bigger significance).
Keywords: balance; experiences; and daily pay-sports